Medium-entropy alloy composite powder for ultrahigh-speed laser cladding, composite coating and application

By designing a medium entropy alloy composite powder system and using Ni to coat the WC ceramic phase, the interface cracking problem caused by the difference in thermal properties between the coating and ceramic phases is solved, and the high hardness and wear resistance of the composite coating are achieved.

CN119464881APending Publication Date: 2025-02-18ARMOR ACADEMY OF CHINESE PEOPLES LIBERATION ARMY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411577604.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the existing ultra-high-speed laser cladding technology, the difference in thermal properties between the coating and ceramics leads to cracking of the contact interface, affecting the performance of the coating performance.

Method used

A medium-entropy alloy composite powder system is designed, including medium-entropy alloy powder and Ni-coated WC powder, which is prepared by aerosolization method and mechanical mixing method to ensure the integrity of the ceramic phase and good combination with the coating.

Benefits of technology

It effectively avoids interface cracking caused by the difference in thermal properties between the coating and the ceramic phase, promotes the dispersion distribution of the ceramic phase and fine crystal strengthening, and significantly improves the hardness and wear resistance of the composite coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464881A_ABST
    Figure CN119464881A_ABST
Patent Text Reader

Abstract

The invention provides medium-entropy alloy composite powder for ultrahigh-speed laser cladding, a composite coating and application. The composite powder comprises medium-entropy alloy powder and Ni-coated WC powder. Wherein the mass fraction ratio of the medium-entropy alloy powder to the Ni-coated WC powder is (1-1.5): 1; the medium-entropy alloy powder comprises Fe, Cr, Ni and Ti, and the molar fraction ratio of Fe to Cr to Ni to Ti is 1: 1: 1: (0.4-0.75). The method has the technical effects that the ceramic strengthening phase is added into a medium-entropy alloy powder system, and in the ultra-high-speed laser cladding process, due to the fact that the laser absorptivity and the heat conductivity of Ni in the composite powder are low, the integrity of the WC ceramic phase is effectively protected, the wettability between the WC ceramic phase and a coating is improved through cladding of Ni, and the corrosion resistance of the WC ceramic phase is improved. And the binding force of a contact interface of the two is effectively enhanced, so that the preparation of the high-hardness and high-wear-resistance ceramic phase compounded medium-entropy alloy coating is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of material surface engineering and additive manufacturing, and specifically relates to a medium-entropy alloy composite powder, a composite coating and an application thereof for ultra-high-speed laser cladding. Background Art

[0002] Ultra-high-speed laser cladding is an emerging surface coating technology. Compared with traditional processes, it has the advantages of low dilution rate, small heat-affected zone, good metallurgical bonding quality, high powder utilization rate and cladding efficiency. In addition, the process is green and environmentally friendly, energy-saving and emission-reducing, so it is widely used in aerospace, automobile manufacturing, petrochemical energy and other fields. While improving the wear resistance, corrosion resistance and thermal stability of parts, it also brings significant economic benefits and has broad application prospects in industrial production. However, in order to obtain ideal high-performance coatings, the selection of cladding materials is also crucial. At present, the cladding materials used in ultra-high-speed laser cladding mostly follow the cladding materials of conventional laser cladding processes, mainly traditional metal alloy powders such as nickel-based alloys, iron-based alloys, and cobalt-based alloys. The system is relatively single and the coating performance improvement effect is limited. With the continuous development and progress of various industries, higher requirements are put forward for the service performance and service life of parts. Therefore, the research and development of cladding materials with excellent performance is one of the important research directions of ultra-high-speed laser cladding technology.

[0003] Medium entropy alloy is a new type of alloy material. Compared with high entropy alloy, it has fewer alloy components and simpler composition design, so it is cheaper. At the same time, it is more conducive to the orderly arrangement and diffusion of atoms in the coating, maintaining a stable crystal structure and phase composition, and has better mechanical properties than high entropy alloys and other traditional alloy materials. Laser cladding CoCrNi medium entropy alloy coating is one of the medium entropy alloy systems that has been invested in research because of its stable face-centered cubic structure and strong yield strength and hardness. Based on this alloy system, adding or replacing one or two elements with different physical and chemical properties for composition design is a conventional method to further improve the comprehensive performance of medium entropy alloy coating. Chongqing University of Technology used pulsed laser cladding to prepare CoCrNiTi and CrFeNiTi medium entropy alloy coatings. Under the strengthening effect of body-centered cubic structure and Laves phase, the hardness of the coating is 6 to 7 times that of the substrate, and the wear resistance is significantly improved. Using the same process, they also studied the refractory medium-entropy alloy CrNiTiZr coating. In addition to obtaining higher hardness and strength, the lower KAM value also reflects the uniformity of the coating structure lattice orientation and the smaller residual stress between grains. It is a surface protective coating with good comprehensive performance.

[0004] In order to further improve the hardness and wear resistance of medium-entropy alloy coatings and enhance the service capability of equipment under extreme working conditions, medium-entropy alloy composite is a new design idea for alloy systems. High-hardness and high-wear-resistant ceramic phase is a commonly used composite material. There are two composite methods: in-situ generation and direct addition. The former has high forming conditions and is not easy to control the content. Therefore, direct addition of ceramic phase is the main composite method. However, in the actual preparation process of composite coatings, due to the difference in thermophysical properties between the coating and the ceramic phase, cracks are prone to appear at the interface between the coating and the ceramic. Some cracks even penetrate the ceramic phase. Similar defects can easily cause the ceramic phase to fall off, thereby affecting the performance of the coating. Therefore, designing a medium-entropy alloy composite powder system for ultra-high-speed laser cladding, which makes the coating microstructure uniform, has good bonding quality, and stable service performance, is of great research significance for improving other comprehensive properties such as coating wear resistance, and will play an important role in practical engineering applications. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art and provide a medium entropy alloy composite powder, a composite coating and an application thereof for ultra-high-speed laser cladding.

[0006] According to a first aspect of the present invention, a medium entropy alloy composite powder for ultra-high speed laser cladding is provided, comprising a medium entropy alloy powder and a Ni-coated WC powder; wherein the mass fraction ratio of the medium entropy alloy powder to the Ni-coated WC powder is (1-1.5):1;

[0007] The medium entropy alloy powder comprises Fe, Cr, Ni and Ti, and the molar fraction ratio of Fe, Cr, Ni and Ti is 1:1:1:0.4-0.75.

[0008] Optionally, the Ni-coated WC powder has a sphericity of 95% to 100% and a particle size distribution range of 45 μm to 105 μm.

[0009] According to a second aspect of the present invention, a method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding is provided, characterized in that it comprises the following steps:

[0010] Weigh Fe, Cr, Ni, and Ti metal powders in a molar fraction ratio of 1:1:1:0.4 to 0.75;

[0011] FeCrNiTi with a preset particle size range is produced by gas atomization x Spherical medium entropy alloy powder; wherein x=0.4-0.75;

[0012] Weigh FeCrNiTi according to the mass fraction ratio of (1-1.5):1 x(x=0.4~0.75) Spherical medium entropy alloy powder and Ni-coated WC powder;

[0013] Using the principle of mechanical mixing, FeCrNiTi x(x=0.4~0.75) The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed, and after being evenly mixed, they are placed in a drying oven for drying to prepare medium entropy alloy composite powder for ultra-high-speed laser cladding.

[0014] Optionally, the purity of the Fe, Cr, Ni, and Ti metal single substance powders is ≥99.9%.

[0015] Optionally, the preset particle size range is 45 μm to 105 μm.

[0016] Optionally, the FeCrNiTi x The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed; wherein, the mixing parameters of the three-dimensional powder mixer are a rotation speed of 60r / min-80r / min, a mixing time of 4h-5h, and a forward and reverse rotation time of 15min each as one cycle.

[0017] Optionally, the drying condition of the drying oven is 65° C. for 5 hours.

[0018] According to a third aspect of the present invention, there is provided an ultra-high speed laser cladding composite coating, which is a composite powder prepared by the method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding as described in the second aspect, comprising: using ultra-high speed laser cladding the composite powder to prepare a composite coating on the surface of a substrate.

[0019] Optionally, the substrate is made of carbon steel or stainless steel.

[0020] According to a fourth aspect of the present invention, there is provided a method for preparing a composite coating, for preparing the composite coating as described in the third aspect, comprising:

[0021] The composite coating is clad on the substrate surface using ultra-high-speed laser; the process parameters of ultra-high-speed laser cladding are as follows:

[0022] The laser power is 1800W-2600W, the scanning speed is 350mm / s-480mm / s, the powder feeding rate is 1.8r / min-2.1r / min, the circular spot diameter is 2.0mm, and the overlap rate is 65%-80%.

[0023] A technical effect of the present invention is:

[0024] In the embodiments of the present application, a ceramic reinforcing phase is added to the medium-entropy alloy powder system, and the WC ceramic phase is coated with Ni. During the ultra-high-speed laser cladding process, since Ni has a low absorption rate and thermal conductivity to laser, the integrity of the WC ceramic reinforcing phase is effectively protected. The Ni coating also improves the wettability between the WC ceramic phase and the coating, effectively enhancing the bonding strength of the contact interface between the two, thereby realizing the design and preparation of a medium-entropy alloy coating composite with a high-hardness and high-wear-resistant ceramic phase.

[0025] Furthermore, the composite coating can effectively avoid the phenomenon of cracking at the contact interface due to the difference in thermal properties between the coating and the ceramic phase, and promote the dispersion distribution of the crack-free WC ceramic phase in the coating, forming dispersion strengthening; at the same time, the ceramic phase, as a heterogeneous nucleation center, promotes the formation of secondary dendrites, increases the nucleation rate, refines the grains, and forms fine-grained strengthening. The above-mentioned strengthening effect and the high strength and hardness of the WC ceramic phase itself significantly improve the hardness of the composite coating.

[0026] In addition, the ceramic reinforcement phase evenly distributed in the composite coating reduces or inhibits the initiation and propagation of cracks by bearing the impact, extrusion and plowing of the counterparts during friction and wear, thereby achieving the excellent wear resistance of the medium-entropy alloy composite coating, thereby effectively responding to application requirements under extreme working conditions, and helping to effectively promote the industrial application of ultra-high-speed laser cladding technology in repairing and strengthening the surface of equipment parts in aerospace, petrochemical, national defense and military, etc., which has important economic and social significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic flow chart of a method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding provided in an embodiment of the present invention.

[0028] Figure 2 A macroscopic surface image of a coating prepared by a medium entropy alloy composite powder for ultra-high speed laser cladding provided by an embodiment of the present invention ( Figure 2 (a)) and surface crack detection diagram ( Figure 2 (b)).

[0029] Figure 3 A macroscopic cross-sectional view of a coating prepared from a medium-entropy alloy composite powder for ultra-high-speed laser cladding provided in an embodiment of the invention.

[0030] Figure 4 A wear rate diagram of a coating and a substrate prepared by a medium entropy alloy composite powder for ultra-high-speed laser cladding provided in an embodiment of the invention. DETAILED DESCRIPTION

[0031] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values ​​set forth in these embodiments do not limit the scope of the present application.

[0032] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.

[0033] According to a first aspect of the present invention, there is provided a medium entropy alloy composite powder for ultra-high speed laser cladding, comprising a medium entropy alloy powder and a Ni-coated WC powder; wherein the mass fraction ratio of the medium entropy alloy powder to the Ni-coated WC powder is 1 to 1.5:1;

[0034] The medium entropy alloy powder comprises Fe, Cr, Ni and Ti, and the molar fraction ratio of Fe, Cr, Ni and Ti is 1:1:1:0.4-0.75.

[0035] In the embodiments of the present application, a ceramic phase is added to the medium-entropy alloy powder system for reinforcement, and Ni is used to coat the WC ceramic phase. During the cladding process, the integrity of the WC ceramic phase is effectively protected due to the low absorption rate and thermal conductivity of Ni to the laser. The Ni coating also improves the wettability between the WC ceramic phase and the coating, effectively enhancing the bonding strength of the contact interface between the two, thereby helping to achieve the design and preparation of a medium-entropy alloy coating composite with a high-hardness and high-wear-resistant ceramic phase.

[0036] For example, assuming that the four elements Fe, Cr, Ni and Ti are weighed in amounts of 1 mol, 1 mol, 1 mol and 0.7 mol respectively, the masses of Fe, Cr, Ni and Ti that need to be weighed are 55.85 g, 52.0 g, 58.69 g and 33.51 g respectively.

[0037] Optionally, the sphericity of the Ni-coated WC powder is 95% to 100%, and the particle size distribution range is 45 μm to 105 μm. This helps to improve the fluidity of the powder and prepare a uniform composite coating, thereby significantly improving the wear resistance, hardness and other properties of the composite coating.

[0038] According to the second aspect of the present invention, see Figure 1 , provides a method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding, comprising the following steps:

[0039] Step S100, weighing Fe, Cr, Ni, and Ti metal single substance powders in a molar fraction ratio of 1:1:1:0.7;

[0040] Step S200, using a gas atomization method to prepare FeCrNiTi particles within a preset particle size range 0.7 Spherical medium entropy alloy powder;

[0041] Step S300, weigh FeCrNiTi in a mass fraction ratio of 3:2 0.7 Spherical medium entropy alloy powder and Ni-coated WC powder;

[0042] Step S400, using the principle of mechanical mixing method, using a three-dimensional powder mixer to mix FeCrNiTi 0.7 The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed, and after being evenly mixed, they are placed in a drying oven for drying to prepare medium entropy alloy composite powder for ultra-high-speed laser cladding.

[0043] In the above embodiment, the preparation method of medium-entropy alloy composite powder for ultra-high-speed laser cladding is reasonably designed, which helps to quickly prepare composite powder with stable performance, and helps to ensure the excellent wear resistance of the composite coating when using the composite powder to prepare the composite coating, and has a higher hardness.

[0044] Optionally, the preset particle size range is 45 μm to 105 μm. This helps to prepare a uniform composite coating, so as to significantly improve the wear resistance, hardness and other properties of the composite coating.

[0045] Optionally, a three-dimensional powder mixer is used to mix FeCrNiTi 0.7 The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed.

[0046] Optionally, the purity of Fe, Cr, Ni, and Ti metal single substance powders is ≥ 99.9%, which better guarantees the cladding quality of the composite coating.

[0047] Optionally, the mixing parameters of the three-dimensional powder mixer are as follows: a rotation speed of 70 r / min, mixing for 5 hours, and a forward and reverse rotation of 15 minutes each as one cycle.

[0048] Optionally, the drying condition of the drying oven is 65° C. for 5 hours, which can better ensure the drying effect of the composite powder.

[0049] In a specific embodiment, first, four metal powders of Fe, Cr, Ni and Ti are sent to a gas atomization powder making device, and the process is controlled through smelting → atomization → powder collection to obtain FeCrNiTi with a particle size range of 45 μm to 105 μm. 0.7 The spherical medium entropy alloy powder has high sphericity and good fluidity.

[0050] Then, FeCrNiTi was weighed at a mass fraction ratio of 1.5:1. 0.7 Powder and Ni-coated WC powder, the two powders are sent to a three-dimensional powder mixer and mixed for 5 hours to make the powders fully mixed. After mixing evenly, put them into a drying oven for drying.

[0051] According to a third aspect of the present invention, there is provided an ultra-high speed laser cladding composite coating, which is a composite powder prepared by the method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding as described in the second aspect, comprising: using ultra-high speed laser to clad the composite powder to form a composite coating on the surface of a substrate.

[0052] In the embodiments of the present application, the composite coating can effectively avoid the phenomenon of cracking of the contact interface due to the difference in thermal properties between the coating and the ceramic phase, and promote the dispersion distribution of the WC ceramic phase without crack defects in the coating, forming dispersion strengthening; at the same time, the ceramic phase, as a heterogeneous nucleation center, promotes the formation of secondary dendrites, increases the nucleation rate, refines the grains, and forms fine grain strengthening. The above-mentioned strengthening effect and the high strength and hardness of the WC ceramic phase itself significantly improve the hardness of the composite coating.

[0053] In addition, the evenly distributed ceramic phase in the composite coating reduces or inhibits the initiation and propagation of cracks by bearing the impact, extrusion and plowing of the counterparts during friction and wear, thereby achieving the excellent wear resistance of the medium-entropy alloy composite coating, thereby effectively responding to application requirements under extreme working conditions, and helping to effectively promote the industrial application of ultra-high-speed laser cladding technology in repairing and strengthening the surface of equipment parts in aerospace, petrochemical, national defense and military, etc., which has important economic and social significance.

[0054] In a specific embodiment, before preparing the coating on the substrate surface, the substrate needs to be pretreated. Exemplarily, the substrate is made of 45 steel and the substrate size is 50×50×5mm. The surface of the substrate is polished with 1000-mesh SiC sandpaper to remove the surface oxide layer and achieve a certain degree of surface roughening to increase the laser absorption rate; after treatment, the surface of the substrate is ultrasonically cleaned with alcohol for 5-8 minutes and dried. Then, a composite coating is formed on the pretreated substrate surface by ultra-high-speed laser cladding.

[0055] In the embodiments of the present application, according to the macroscopic morphology of the composite coating and the surface crack detection results, the coating has no surface macroscopic cracks, low surface roughness, and high coating formability. Figure 2 shown.

[0056] According to the cross-sectional morphology of the coating, the WC ceramic phase in the coating maintains a high degree of sphericity and is well bonded to the coating, without defects such as cross-sectional macroscopic cracks. Figure 3 shown.

[0057] Optionally, the substrate is made of carbon steel or stainless steel.

[0058] According to a fourth aspect of the present invention, there is provided a method for preparing a composite coating, for preparing the composite coating as described in the third aspect, comprising:

[0059] The composite coating is clad on the substrate surface by ultra-high-speed laser cladding; the process parameters of ultra-high-speed laser cladding are as follows:

[0060] The laser power is 2400W, the scanning speed is 350mm / s, the powder feeding rate is 2.1r / min, the spot is a circular spot with a diameter of 2.0mm, and the overlap rate of multi-pass cladding is 80%.

[0061] In the above implementation manner, a composite coating with uniform thickness and stable performance can be formed, thereby better ensuring that the composite coating has better properties such as wear resistance and hardness.

[0062] It should be noted that the present invention is based on FeCrNiTi x A new medium-entropy alloy composite powder system for ultra-high-speed laser cladding—FeCrNiTi x / Ni-WC (Ni coated WC ceramic particles) composite powder and its composite coating, and compared the matrix, FeCrNiTi 0.7 / Ni-WC composite coating and FeCrNiTi reinforced by WC ceramic phase without Ni coating 0.7 The friction coefficient and wear loss of the WC / WC composite coating were compared, and the results showed that the new composite coating designed by the present invention has better friction and wear performance. Figure 4 shown.

[0063] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A medium entropy alloy composite powder for ultra-high speed laser cladding, characterized in that: It comprises a medium entropy alloy powder and a Ni-coated WC powder; wherein the mass fraction ratio of the medium entropy alloy powder to the Ni-coated WC powder is 1 to 1.5:1; The medium entropy alloy powder comprises Fe, Cr, Ni and Ti, and the molar fraction ratio of Fe, Cr, Ni and Ti is 1:1:1:0.4-0.

75.

2. The medium entropy alloy composite powder for ultra-high speed laser cladding according to claim 1, characterized in that: The sphericity of the Ni-coated WC powder is 95% to 100%, and the particle size distribution range is 45 μm to 105 μm.

3. A method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding, characterized in that: The steps include: Weigh Fe, Cr, Ni, and Ti metal powders in a molar ratio of 1:1:1:0.4 to 0.75; FeCrNiTi with a preset particle size range is produced by gas atomization x Spherical medium entropy alloy powder; wherein x=0.4-0.75; Weigh FeCrNiTi according to the mass fraction ratio of 1 to 1.5:1 x Spherical medium entropy alloy powder and Ni-coated WC powder; FeCrNiTi was prepared by mechanical mixing x The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed, and after being evenly mixed, they are placed in a drying oven for drying to prepare medium entropy alloy composite powder for ultra-high-speed laser cladding.

4. The method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding according to claim 3, characterized in that: The preset particle size range is 45μm to 105μm.

5. The method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding according to claim 3, characterized in that: Using the principle of mechanical mixing, FeCrNiTi x The spherical medium entropy alloy powder and the Ni-coated WC powder are fully mixed; wherein, the powder mixing parameters of the three-dimensional powder mixer are a rotation speed of 60r / min-80r / min, a powder mixing time of 4h-5h, and a forward and reverse rotation time of 15min each as one cycle.

6. The method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding according to claim 3, characterized in that: The purity of Fe, Cr, Ni and Ti metal single substance powders is ≥99.9%.

7. The method for preparing medium entropy alloy composite powder for ultra-high speed laser cladding according to claim 3, characterized in that: The drying condition of the drying oven is 65°C for 5 hours.

8. An ultra-high-speed laser cladding composite coating, characterized in that: The composite powder is prepared by the method for preparing medium-entropy alloy composite powder for ultra-high speed laser cladding as described in any one of claims 3 to 7, comprising: using ultra-high speed laser cladding the composite powder to prepare a composite coating on the surface of a substrate.

9. The composite coating according to claim 8, characterized in that: The material of the substrate is carbon steel or stainless steel.

10. A method for preparing an ultra-high-speed laser cladding composite coating, characterized in that: For preparing the composite coating according to any one of claims 8 to 9, comprising: The composite powder is clad on the substrate surface using ultra-high-speed laser. The process parameters of ultra-high-speed laser cladding are as follows: The laser power is 1800W-2600W, the scanning speed is 350mm / s-480mm / s, the powder feeding rate is 1.8r / min-2.1r / min, the circular spot diameter is 2.0mm, and the overlap rate is 65%-80%.

Citation Information

Cited By

  • Preparation method of ceramic alloy powder

    CN120885695A